ENGLISH TEACHER AGENCY AND COMPETENCIES IN IMPLEMENTING KURIKULUM MERDEKA AT SENIOR HIGH SCHOOLS IN PALEMBANG, SOUTH-SUMATERA, INDONESIA - Theriana, Ana; Amiruddin, Amiruddin; Fitriati, Sri Wuli; Haryanti, Rahayu Puji ,; Rustipa, Khatarina (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
study aims to examine teacher agency and its influence on teacher competence in the implementation of Merdeka Curriculum in Indonesia. The study involved English teachers at the secondary school level as research subjects, who were divided based on their response to curriculum change: proactive, reactive and passive. The results show that teachers with proactive teacher agency adapt more quickly and are able to develop their pedagogical, social and professional competencies better. They take advantage of the freedom offered by Merdeka Curriculum to innovate in teaching and integrate technology and interactive learning methods. In contrast, teachers with reactive responses require more support in the form of training, time and resources to adjust to the changes, while teachers with passive responses tend to maintain traditional teaching methods and show resistance to change, which hinders the development of their competencies. The implications of these findings suggest the importance of providing ongoing training, adequate resources and collaboration among teachers to support the successful implementation of Merdeka Curriculum. Structural support and better communication between schools and teachers are needed to ensure that all teachers, regardless of their level of teacher agency, can contribute effectively to the implementation of tThis he new curriculum